2016
DOI: 10.3399/bjgp16x684817
|View full text |Cite
|
Sign up to set email alerts
|

Low hepatitis B testing among migrants: a cross-sectional study in a UK city

Abstract: BackgroundIn 2012, hepatitis B virus (HBV) testing of people born in a country with a prevalence of ≥2% was recommended in the UK. Implementation of this recommendation requires an understanding of prior HBV testing practice and coverage, for which there are limited data. AimTo estimate the proportion of migrants tested for HBV and explore GP testing practices and barriers to testing. Design and settingA cross-sectional study of (a) migrants for whom testing was recommended under English national guidance, liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 18 publications
3
33
1
Order By: Relevance
“…The asymptomatic nature of the disease until its late stages and the lack of awareness of risk among migrants and often also among health care providers limit early detection. Other barriers to screening include language, health care access and entitlement issues, high work-load among health care staff, and the potential stigma or fear associated with being diagnosed positive [ 26 , 27 ]. The EU-funded HEPscreen project describes four different screening approaches: (i) outreach screening (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The asymptomatic nature of the disease until its late stages and the lack of awareness of risk among migrants and often also among health care providers limit early detection. Other barriers to screening include language, health care access and entitlement issues, high work-load among health care staff, and the potential stigma or fear associated with being diagnosed positive [ 26 , 27 ]. The EU-funded HEPscreen project describes four different screening approaches: (i) outreach screening (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This is despite the availability of national guidelines for the screening of high-risk groups – including migrants – in the primary care context and secondary-care settings, particularly for HIV testing, which is being advocated for across healthcare settings including emergency departments [ 22 , 59 ]. This is supported by the work of others: in one study exploring hepatitis B screening in a primary care setting, only 9627 (12%) of 82561 migrants eligible for screening in accordance with national guidelines migrants were offered screening by clinicians, with lack of knowledge and lack of resourced cited by clinicians as key barriers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest high acceptability of screening for LTBI and other infections among migrants [ 21 ]. However, formal on-arrival screening programmes miss many migrant groups, with evidence of significant barriers to migrant engagement with primary care where screening is routinely delivered [ 12 , 25 ], and lack of consistency in provision of screening [ [26] , [27] , [28] , [29] , [30] ]. There remain significant evidence-gaps around effective and cost-effective approaches to implementing TB and other infectious diseases screening and ensuring successful treatment outcomes [ 6 , 21 , 24 , [31] , [32] , [33] ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless the evidence is compelling and strong enough to recommend implementation and moving to phase IV evaluation. 'Treatment as usual' is failing to screen migrant populations -in the HepFree control less than 2% of patients were screened -and other studies also have shown low levels of screening except for pregnant women (because there is a commissioned universal antenatal HBV screening programme in the UK) 8 . Local commissioners and primary care services need help on how to take forward NICE guidance.…”
mentioning
confidence: 99%